OUTBREAK OF ZIKA VIRUS DISEASE AND ITS COMPLICATIONS - Gabriela S. Tsankova; Zekie Kasimova; Tatina T. Todorova; Milena Avdzhiyska; Dajna Tsankova (Peytchinski Publishing, 2016)
Zika virus (ZIKV) is an arbovirus from Flaviviridae family, genus Flavivirus. Like most of the viruses which belong to the Flavivirus genus, it replicates in and is transmitted by mosquitoes. Unlike other arbovirus infections including dengue and chikungunya, Zika virus causes a relatively mild disease. The most common symptoms of ZIKV are mild fever, arthralgia, myalgia, headache, asthenia, abdominal pain, oedema, lymphadenopathy, retro-orbital pain, conjunctivitis, and cutaneous maculopapular rash, which last for several days to a week. Although 80% of the cases with ZIKV are asymptomatic, severe complications such as microcephalia and GBS may be observed. This explains why ZIKV is more dangerous that it was thought to be and why it rapidly evolves in unexpected challenge for the international and national public health authorities.